(untitled) (Journal of Partial Differential Equations, 2014)
" In this paper, we study how the shape of the graph of a(z) affects on the number of positive solutions of - Delta upsilon+03bc b(z) upsilon^p-1+03bb h(z) upsilon^q-1, qquad ;in ; mathbbR^N. qquad (0.1) We prove for large enough 03bb,03bc 203a 0, there exist at least k+1 positive solutions of the this semilinear elliptic equations where 1 2264 q 2039 2 2039 p 2039 2*|=2N\/(N-2) for N 2265 3."